(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The urbanization processes and its keen relationship with the spatio-temporal variability of land use-land cover (LULC), land surface temperature and urban heat island (HI) within the district towns in the Rangpur division of Bangladesh has been assessed using multi-spectral Landsat satellite images from 1991 to 2021.The supervised classification approach was used to retrieve LULC types such as water body, built-up area, bare land, agricultural land and vegetation cover. The results of LULC suggest that agricultural and bare land have decreased during the last 30 years in the study areas. The vegetation cover shows an average increase and built-up area has increased progressively from 1991 to 2021. Conspicuously the water bodies, agricultural and bare lands have reduced due to the expansion and rapid growth of settlement areas or urbanization. The spatio-temporal variability of Land Surface Temperature (LST) over the study area responsible for the development of the urban heat islands (UHIs) is assessed using the mono-window algorithm. The areal extents of the UHIs are spreading out day by day and have become most extensive in 2021. Correlation of LULC types with the HI and LST indicated that lower temperature zones were found in the water bodies, vegetated and agricultural lands whereas higher temperature zones were found in the bare lands or highly built-up areas within the district towns. Ground truth data have been validated well with the image processed results with an overall 86.25% classification accuracy which indicates a good level of accuracy of the detected LULC using satellite images. Thus, the research work will help in understanding the land cover dynamics, increasing LST and heat island growth, which could be further used for mitigating the socio-economic hazards faced by the communities in and around the study areas. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 17-28